Hyperthermic intraperitoneal chemotherapy for ovarian cancer: The heat is on. (3rd December 2019) - Koole, Simone N.; van Driel, Willemien J.; Sonke, Gabe S.
Abstract : Patients with advanced epithelial ovarian cancer have a high incidence of peritoneal disease recurrence despite maximal efforts to surgically remove all visible tumor plus intravenous chemotherapy. The administration of intraperitoneal chemotherapy that specifically targets the peritoneal surface has been investigated in previous trials, but questions about the design of these studies has prevented this treatment from being widely adopted in clinical practice. Hyperthermic intraperitoneal chemotherapy (HIPEC) is a single intraoperative approach that also targets the peritoneal surface. A randomized phase 3 trial showed significant benefit in recurrence‐free and overall survival when HIPEC was added to interval cytoreductive surgery (CRS) in patients who were not eligible for primary surgery because of the extent of their disease (OVHIPEC trial; NCT00426257). The trial showed no important differences in toxicity or patient‐reported outcomes between the study groups. The extent of surgery and the number of bowel resections were also similar between the 2 study groups, and the effect of HIPEC was homogeneous across the levels of predefined and post hoc subgroups. Nevertheless, the design and the results of the OVHIPEC trial were critically assessed, and this resembles the reluctance to adopt the positive results of the earlier intraperitoneal chemotherapy studies. This overview discusses the design and results of the OVHIPEC trial. The evidence that is currently available points to a clinically relevant and cost‐effective benefit of HIPEC added to interval CRS for patients with stage III ovarian cancer who are not eligible for primary surgery. Ongoing collaborative research will provide further evidence regarding the role of HIPEC in ovarian cancer. Abstract : This review discusses the design and results of a phase 3 randomized trial in HIPEC for patients with ovarian cancer (OVHIPEC trial; NCT00426257). The evidence that is currently available points to a clinically relevant and cost‐effective benefit of hyperthermic intraperitoneal chemotherapy added to interval cytoreductive surgery for patients with stage III ovarian cancer who are not eligible for primary surgery.